2020
DOI: 10.3892/ol.2020.12094
|View full text |Cite
|
Sign up to set email alerts
|

Identification of diagnostic and prognostic biomarkers, and candidate targeted agents for hepatitis B virus‑associated early stage hepatocellular carcinoma based on RNA‑sequencing data

Abstract: Primary liver cancer is a rapidly progressing neoplasm with high morbidity and mortality rates. The present study aimed to identify potential diagnostic and prognostic biomarkers, and candidate targeted agents for hepatitis B virus (HBV)-associated early stage hepatocellular carcinoma (HCC). The gene expression profiles were extracted from the Gene Expression Omnibus database. Differentially expressed genes (DEGs), hub genes and the enrichment of signaling pathways were filtered out via a high-throughput seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 94 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…Figure 1B; Suppl. File 1) (Jiang et al, 2019; Zeng et al, 2020). Consistent with a prior observation (Villemin et al, 2023), a greater number of LRIs were detected in scRNA-seq data, with bulk RNA-sequencing contributing a modest number of unique LRIs (Suppl.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1B; Suppl. File 1) (Jiang et al, 2019; Zeng et al, 2020). Consistent with a prior observation (Villemin et al, 2023), a greater number of LRIs were detected in scRNA-seq data, with bulk RNA-sequencing contributing a modest number of unique LRIs (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…A count matrix of bulk RNA-seq dataset of CHB HCC tissue samples (Jiang et al, 2019; Zeng et al, 2020) was downloaded from GEO under the ascension number GSE124535. The count matrix contained FPKM values of 35 HCC liver tissue samples and was used to infer LRIs with the R package BulkSignalR as described with the parameter “normalize=FALSE” in the “prepareDataset” function.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through connectivity map analysis, several small molecule compounds were identified that might reverse the changes in DEGs, including benzoxybenzylamine, GW-8510, resveratrol, 0175029-0000, and rosiglitazone. Considering the critical role that dysfunctions in fatty metabolism pathways, cell cycle, oxidation-reduction processes, and viral carcinogenesis may play in the development of HBV-related early HCC, the study proposed that the identified eight hub genes (CDC20, CCNB1, AURKB, CCNA2, CDK1, APOA1, UBB, EHHADH) could serve as potent biomarkers and therapeutic targets for diagnosis and prognosis [31].…”
Section: In the Exploration Of New Biomarkers And Targetsmentioning
confidence: 99%
“…Numerous studies have revealed that tumorigenesis and cancer progression are usually accompanied by abnormal regulation of the PPAR signaling pathway [9][10][11][12]. In addition, in recent studies on HCC prognostic markers, it has been repeatedly reported that the PPAR signaling pathway is dysregulated in highrisk HCC patients with poor prognosis [13][14][15]. Although the PPAR signaling pathway has been reported as one of the prognostic characteristic pathways of HCC, no one has screened the prognostic markers for HCC from the genes involved in this pathway.…”
Section: Introductionmentioning
confidence: 99%